2010
DOI: 10.1016/j.jcrs.2010.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcome and patient satisfaction after multifocal intraocular lens implantation: Aspheric versus spherical design

Abstract: Patients with the aspheric multifocal IOL had significantly better near vision than patients with the multifocal spherical IOL. The UDVA, CDVA, intraocular straylight, night-vision symptoms, and contrast sensitivity were similar between the 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 39 publications
0
22
0
2
Order By: Relevance
“…Several authors have used the phakic straylight reference curve in their research to compare the straylight value in pseudophakic eyes. 10,21,24,26,29,30 However, when comparing the pseudophakic curve with the phakic curve, there are important differences. Straylight levels are stable in young phakic eyes and increase considerably above the age of 50 years; thus, the phakic reference is approximated by a logarithmic function.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have used the phakic straylight reference curve in their research to compare the straylight value in pseudophakic eyes. 10,21,24,26,29,30 However, when comparing the pseudophakic curve with the phakic curve, there are important differences. Straylight levels are stable in young phakic eyes and increase considerably above the age of 50 years; thus, the phakic reference is approximated by a logarithmic function.…”
Section: Discussionmentioning
confidence: 99%
“…No differences in straylight have been detected for spherical compared to aspheric IOLs. 14,15 In a study in which subject age was taken into account, multiple linear regression analysis using log straylight as the dependent variable revealed that both age and IOL type had an effect on the amount of straylight generated. 11 Few studies have centered on obtaining objective halo size measurements in subjects implanted with an intraocular lens.…”
mentioning
confidence: 99%
“…De Vries et al 21 showed that there was no difference between spherical and aspheric multifocal IOLs with a similar material and Straylight Measurements/Lapid-Gortzak et al diffractive pattern with respect to the mean straylight value. Van Gaalen et al reported similar outcomes, but their study included only monofocal IOLs.…”
Section: Straylight Measurements/lapid-gortzak Et Almentioning
confidence: 97%
“…The comparison of multifocal apodized diffractive IOLs from the same manufacturer, differing only in its effect on spherical aberration, have shown no difference in straylight. 21 Most of these studies were done with small cohorts, and have shown different results in terms of straylight when using different types of lenses. As a result, the effect of multifocality on straylight is unclear.…”
Section: Straylight Measurements/lapid-gortzak Et Almentioning
confidence: 99%